Glacial isostatic adjustment in the static gravity field of Fennoscandia. Issue 1 (7th January 2015) - Root, B. C.; van der Wal, W.; Novák, P.; Ebbing, J.; Vermeersen, L. L. A.
Abstract In the central part of Fennoscandia, the crust is currently rising, because of the delayed response of the viscous mantle to melting of the Late Pleistocene ice sheet. This process, called Glacial Isostatic Adjustment (GIA), causes a negative anomaly in the present‐day static gravity field as isostatic equilibrium has not been reached yet. Several studies have tried to use this anomaly as a constraint on models of GIA, but the uncertainty in crustal and upper mantle structures has not been fully taken into account. Therefore, our aim is to revisit this using improved crustal models and compensation techniques. We find that in contrast with other studies, the effect of crustal anomalies on the gravity field cannot be effectively removed, because of uncertainties in the crustal and upper mantle density models. Our second aim is to estimate the effects on geophysical models, which assume isostatic equilibrium, after correcting the observed gravity field with numerical models for GIA. We show that correcting for GIA in geophysical modelling can give changes of several kilometer in the thickness of structural layers of modeled lithosphere, which is a small but significant correction. Correcting the gravity field for GIA prior to assuming isostatic equilibrium and inferring density anomalies might be relevant in other areas with ongoing postglacial rebound such as North America and the polar regions.